SUSTAINABILITY OF COOPERATIVES AND DONOR SUPPORT: THE ‘WAIT-AND-SEE” ATTITUDE OF MEMBERS - Ojiagu, Nkechi C.; Arinze Victor Chijioke, (NIGERIAN JOURNAL OF COOPERATIVE ECONOMICS AND MANAGEMENT, 2023)
The recognition of Cooperatives as a crucial means of promoting sustainable livelihoods which is strongly linked with income-generation activities for individuals and the community has been widely acknowledged. Hence, cooperatives are exploring means to guarantee that their entities will last long to continually provide members need and create value consistent with the long-term preservation and enhancement of financial, environmental and social capital, even, in today's competitive environment. Trends such as climate change, globalization, demographic change and social inequity have created a significant challenge to the traditional business model with its focus on owners' value. Hitherto, the sustainability of cooperatives becomes imperative, especially in rural scenarios with shocking issues of dormancy, moribund, extinctions and mismanagement which are widespread. The sustainability of cooperatives connotes “keep the business” or “future-proofing” which involves equity between members and equity within members. But donor support (government paternalism) to cooperatives has extremely challenged the goals of economic and social development of these enterprises hence members attitude of “wait-and-see” syndrome not trying to tap into a fresh revenue stream. This attitude of members no doubt is mostly occasioned by lack of education and training, and effective membership participation. This research work finds its crux through genuine efforts to contribute knowledge to current discourse. The paper is a descriptive study which anchors on theoretical considerations.